Republic of Croatia : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Croatia. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses the economic developments, outlook, risk, and policies of Croatia. This East European country has begun since the last quarter of 2014 to gradually recover from a six-year recession. In 2015 real GDP grew by 1.6 percent, driven by strong exports and tourism, a revival of private consumption, and higher public investment. Consumer prices have largely been declining over the past two years, mainly due to lower energy and food prices. Unemployment declined only slightly since 2014 and remains very high. However, absent concrete measures to underpin some of the planned reforms, slightly higher deficit in 2016 and a slower pace of consolidation over the medium term are projected.